👤

3. If the remainder after dividing polynomial (5x^3 – 3x + k) by (x + 1) is 4, which
of the following must be the value of K?
B. 11
C. 12
D 13​


Sagot :

Answer:

The remainder is 6

Step-by-step explanation:

Note that x+1 = 0 , will be x = -1

Now , the expression 5x³-3x+k = 4

  • We will substitute the value of x which is -1

Solving ,

  • 5x³-3x+k = 4
  • 5(-1)³-3(-1)+k = 4
  • 5(-1) +3 +k = 4
  • -5 + 3+k = 4
  • -2+k = 4
  • k = 4+2
  • k = 6

Checking:

  • 5x³-3x+6 = 4
  • 5(-1)³-3(-1)+6 = 4
  • 5(-1) +3 + 6 = 4
  • -5 + 3 + 6 = 4
  • -2 + 6 = 4
  • 4 = 4